Evaluation of the relationship between pneumatization of mastoid process, articular eminence and glenoid fossa on CBCT - Kontanli, Sedef; Yalçin, Eda Didem (Universitas Airlangga, 2025)
Background: Pneumatization refers to air-filled spaces within the bone. The studies about articular tubercle/eminence pneumatization were only few in numbers with unclear information regarding the data on pneumatization in this region. PAT may become predisposed to the spread of inflammatory processes along the temporomandibular joint. Traumatic occlusion, one of the triggers of the TMJ inflammatory process, can occur during conservative dentistry treatment which requires the attention of a dentist to avoid TMJ disorder. Objectives: This study aimed to evaluate the prevalence, characteristics and relationships of mastoid process pneumatization (MPP), articular tubercle/eminence pneumatization (PAT), and glenoid fossa pneumatization (PGF) in one population in Turkey by using cone-beam computed tomography (CBCT). Methods: In total, 739 of CBCT images were examined retrospectively. The prevalences of the pneumatization by age, gender, laterality and locularity were detected. Independent t-test and the chi-square test for the significance of differences between variables. Results: Apneumatic type MPP was detected in 3.1% of cases, partial pneumatic type MPP in 33.6%, pneumatic type MPP in 63.3% of cases. PGF was detected in 28.0% of the sides and PAT in 23.7% of cases. There was no statistically significant relationship found between the presence of PAT and PGF with gender and age (p>0.05). In 45 cases with a pneumatic type MPP, PGF was not observed in any of them, while no PAT was determined in 44 (97.8%) of 45 cases. Pneumatic type mastoid was detected in 309 (92.8%) of 333 cases with multilocular PGF and in 89 (82.4%) of 108 cases with unilocular PGF. There was a statistically significant relationship found between MPP and PAT with PGF types (p <0.05). Conclusion: It is necessary to detect these air gaps before TMJ surgery to prevent complications during and after the operation. It will be more accurate if PAT and PGF are assessed on 3D technics than on 2D radiographs. Relationship between MPP pneumatization degree and PAT and PGF can help for understanding the features and functions of PAT and PGF, it has been considered useful to also determine the prevalence and characteristics of PAT in a population of traumatic patients of occlusion treatment and to examine the possible relationship between traumatic types of occlusions and pneumatized articular eminence.